Eco-design and eco-manufacturing consulting microenterprises as part of the circular economy strategy - role and risks - Dijmarescu, Manuela Roxana (Technium Social Sciences Journal, 2020)
Over the last decades, a high degree of importance was given to the sustainable development of our world. At European level, the European Union developed a series of standards and fiscal regulations in order to support the achievement of sustainable development goals. An important step is the transition from a linear economy to a circular economy and a primary role in this transition is played by the adaptation of design and manufacturing processes to modern environmental and energy efficiency standards. This process of transformation can be achieved either by an internal department working within the company or by a specialised third-party consulting company. The second option is preferable due to the fact that it does not require a further specialisation process for some employees in order to enable the company to develop a project. As a response to these market requirements, at a European level, within the Common Market, specialised consulting companies started to emerge and develop. This paper details the role and the risks a consulting services microenterprise active in the field of eco-design and eco-manufacturing has to assume in the current socio-economic context; particularly in regard to factors that facilitate the transition from a linear economy to a circular economy.